The impact of Covid-19 on the mental health of professional footballers - Souter, G.; Tonge, A.; Culvin, A. (Managing Sport and Leisure, 2021)
The Covid-19 pandemic has had huge ramifications on professional football. This commentary focuses on the impact of the pandemic on the mental health of professional footballers. Specifically, footballers within the English Premier League, English Football League, FA Women`s Super League and FA Women`s Championship. This commentary considers a holistic approach to mental health, the environment of professional football, and the impact of career transitions and critical moments on mental health. The intention is to stimulate discussion and further research of mental health and wellbeing within professional football. This paper considers the impact of Covid-19 and makes recommendations for professional football clubs to develop a holistic mental health strategy. We recommend that professional clubs increase the level of emotional support for professional footballers, and that this should not be a temporary measure due to the pandemic. Clubs should develop a long-term strategy to encourage players to seek emotional support.